2017
DOI: 10.1136/bmj.j1456
|View full text |Cite
|
Sign up to set email alerts
|

Association between active commuting and incident cardiovascular disease, cancer, and mortality: prospective cohort study

Abstract: ObjeCtiveTo investigate the association between active commuting and incident cardiovascular disease (CVD), cancer, and all cause mortality. DesignProspective population based study.PartiCiPants 263 540 participants (106 674 (52%) women; mean age 52.6), recruited from 22 sites across the UK. The exposure variable was the mode of transport used (walking, cycling, mixed mode v non-active (car or public transport)) to commute to and from work on a typical day. Main OutCOMe MeasuresIncident (fatal and non-fatal) C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
283
1
27

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(324 citation statements)
references
References 15 publications
13
283
1
27
Order By: Relevance
“…However, while many existing bicycle studies focus on identifying built environment factors that affect the bicycle use [30] [31], to the authors' knowledge, very little research has yet been conducted on how positive health benefits may be a factor in influencing commuters to cycle to work [32]. In particular, even though our study focused on employing extrinsic rewards (e.g., money) for stimulating commuting to work by bike; based on the results here presented, the authors believe that health benefits could potentially be used as a powerful intrinsic reward to persuade car drivers to choose the bicycle over the car.…”
Section: Feeling Healthy Is An Important Reason To Cycle To Workmentioning
confidence: 99%
“…However, while many existing bicycle studies focus on identifying built environment factors that affect the bicycle use [30] [31], to the authors' knowledge, very little research has yet been conducted on how positive health benefits may be a factor in influencing commuters to cycle to work [32]. In particular, even though our study focused on employing extrinsic rewards (e.g., money) for stimulating commuting to work by bike; based on the results here presented, the authors believe that health benefits could potentially be used as a powerful intrinsic reward to persuade car drivers to choose the bicycle over the car.…”
Section: Feeling Healthy Is An Important Reason To Cycle To Workmentioning
confidence: 99%
“…Prospective studies comparing the benefits of walking vs cycling suggest that cycling may provide greater health benefits than walking in healthy individuals 10, potentially through the higher intensity of cycling which leads to increased fitness 11; however, there are a number of barriers, including hilly routes and perceived effort, which are likely to discourage people with Type 2 diabetes from cycling.…”
Section: Introductionmentioning
confidence: 99%
“…The median intensity for commutes ranged from 1.28 MET for car commuters to 6.44 MET for cyclists. In 2017 an extensive study from Glasgow (Celis-Morales et al, 2017), which investigated data from more than 260,000 participants, attracted a great deal of attention. The authors found that active commuting cut the risk for all-cause mortality massively.…”
Section: Literature Reviewmentioning
confidence: 99%